Nipah virus outbreak in India: is it a bat-man conflict? - Narayan, Vinod A. (International Journal Of Community Medicine And Public Health, 2019)
Nipah virus infection is a newly emerging zoonotic disease that spreads from animal to human. The fruit bats are the one of the carriers of Nipah virus which gets transmitted from bats to other animals mainly through body fluids. Nipah can cause asymptomatic infection to the acute respiratory syndrome and fatal encephalitis in human beings with a dreadful mortality rate of 70 per cent. This review article focused on role of bats in ecosystem and preventive measure to contain the virus by improving public health. In 2018 the outbreak of Nipah in Kerala state of India claimed 17 lives. It has indeed opened Pandora’s box exposing the role of general public, health department and social media and so on. The early detection and the well-oiled medical infrastructure in the state did wonders. Though social media have been accused of spreading misinformation leading to culling of bats, the people of Kerala responded with positive frame of mind. Prompt and synchronized efforts of all stakeholders like health workers, state government, scientists, researchers and central government led to timely and successful control of Nipah virus cases in Kerala.